Serious gaming to stimulate participatory urban tourism planning. Issue 9 (15th June 2022) - Koens, Ko; Klijs, Jeroen; Weber-Sabil, Jessika; Melissen, Frans; Lalicic, Lidija; Mayer, Igor; Önder, Irem; Aall, Carlo
Abstract: This paper examines how a serious game approach could support a participatory planning process by bringing stakeholders together to discuss interventions that assist the development of sustainable urban tourism. A serious policy game was designed and played in six European cities by a total of 73 participants, reflecting a diverse array of tourism stakeholders. By observing in-game experiences, a pre- and post -game survey and short interviews six months after playing the game, the process and impact of the game was investigated. While it proved difficult to evaluate the value of a serious game approach, results demonstrate that enacting real-life policymaking in a serious game setting can enable stakeholders to come together, and become more aware of the issues and complexities involved with urban tourism planning. This suggests a serious game can be used to stimulate the uptake of academic insights in a playful manner. However, it should be remembered that a game is a tool and does not, in itself, lead to inclusive participatory policymaking and more sustainable urban tourism planning. Consequently, care needs to be taken to ensure inclusiveness and prevent marginalization or disempowerment both within game-design and the political formation of a wider participatory planning approach.